Effectiveness and safety of acupotomy on lumbar spinal stenosis: A pragmatic randomized, controlled, pilot clinical trial: A study protocol. Issue 51 (23rd December 2021) - Han, Ji Hoon; Lee, Hyun-Jong; Woo, Sang Ha; Park, Yu-kyeong; Choi, Ga-Young; Heo, Eun Sil; Kim, Jae Soo; Lee, Jung Hee; Park, Chung A.; Lee, Woo Dong; Yang, Chang Sop; Kim, Ae-Ran; et al.
Abstract: Introduction: Lumbar spinal stenosis (LSS) is a pathological condition that causes a variety of neurological symptoms due to narrowing of the anatomical structures; usually, conservative treatment is recommended, rather than surgical treatment. Acupotomy combines conventional acupuncture with small scalpels; the procedure can be considered minimally invasive, and has recently received considerable attention in clinical practice. Still, there is a lack of data and randomized controlled trials regarding acupotomy related to LSS. Additional studies are necessary, considering the low methodological quality and small size of the study. Methods and analysis: This is a pragmatic, pilot, randomized controlled trial. The trial comprises 8 weeks of treatment, with 16 visits and a 4-week follow-up period. Forty participants diagnosed with LSS will be randomly assigned to either the experimental or control groups; both groups will receive acupuncture and interferential current therapy twice a week for 8 weeks, while the experimental group will receive an additional acupotomy intervention once a week for 8 weeks. The primary outcome will be assessed using the visual analog scale; the secondary outcome will be measured by self-rated walking distance, Oswestry Disability Index, and short-form McGill Pain Questionnaire. Measurements will be obtained prior to the start of the clinical trial, 4 weeks after the interventional procedure, 8 weeks after the procedure, and 4 weeks after the end of the interventional procedure. Blood tests and adverse reactions will be performed to ensure safety of the treatments. Conclusion: We expect that this study will provide basic data for future large-scale acupotomy studies regarding LSS.